An approach for an algebra applied to a defeasible logic programming - Budán, Maximiliano Celmo David (2012)
In the last decade, several argument-based formalisms have emerged, with application in many areas, such as legal reasoning, au- tonomous agents and multi-agent systems. In this work we present an approach applied to any concrete argumenta- tion systems, called Argumentative Labels Algebra (ALA), in which propagate certain information through the internal structure of the argument and the existing relations between these. This information can be used for di erent proposed: (1) determine which argument defeat another, analyzing a feature that is relevant to the domain (eg. time availability, degree of reliability, particular characteristics, among others) and (2) de ne a acceptability threshold which will determine if the arguments are strong enough to be accepted. For this way, we obtain an approach that strengthens the argumenta- tions systems, increase the ability of real-world representation modeling di erent attributes associated to the arguments.